Sikhs’ Social Role and their Impact in Kenya’s Sustainable Development, 1895-1990 - publisher, publisher (African Journal of Education,Science and Technology (AJEST), 2017)
The Sikh communities are people with a history. In India, Sikhs have attracted various studies particularly because of their diverse role. The same has been done on the diaspora Sikh in Europe, America, Australia, and Africa. This study was motivated by the fact that, the Sikh left India, went abroad, remained a distinct religious community, established themselves, affected the host societies in varying degrees and most importantly, attracted multi racial scholarly attention from a cross section of disciplines including history, sociology and religious studies, that is largely reflecting their diverse effects in a series of fields. However, scholarly coverage of the Sikhs in Kenya, more specifically the interrogation of their social impact 1895-1990, since their coming to the then Imperial British East Africa (IBEA) is scanty. Sikhs influx to Kenya followed British control and expansion from the East Coast of Africa to the interior of what became Kenya, it was necessitated by increased demand for Indian labour force which was designated by William Mackinnon of IBEA company to work on the Kenya-Uganda railway. The paper investigates the Sikh’s social institutions, temples, Sikhs’ role in education, health and sports in Kenya. The study was informed by Humanistic model. Data was collected from both primary and secondary sources. Non-probability, purposive sampling procedures specifically snowball were engaged. Informants involved were specific people who were in a position of being conversant with research problem yet were scattered in major urban centres in Kenya. Observation and Interview guide instruments were used. Data was analyzed qualitatively as was envisaged in descriptive research design applied in this study. The findings of the study are an addition to Sikh historiography and a contribution to knowledge. The paper brings to the fore unique, distinct social institutions of the Sikh community as people with a role to play to the larger Kenyan society.